Efficient Thiophene Synthesis Mediated by 1, 3‐Bis(carboxymethyl)imidazolium Chloride: C‐C and C‐S Bond Formation. Issue 28 (14th July 2020) - Gisbert, Patricia; Pastor, Isidro M.
Abstract : Thiophene derivatives have been prepared by means of a functionalized imidazolium salt [1, 3‐bis(carboxymethyl)imidazolium chloride] acting as a catalyst. The heterogeneous catalyst has allowed to carry out the reactions with no solvent or inert atmosphere. Different aryl methyl ketones have reacted with elemental sulfur to selective produce 2, 4‐substituted thiophenes. Furthermore, the reaction of sulfur with cyclic ketones has enabled the preparation of polycyclic compounds. This protocol is simple and effective for preparing thiophene derivatives, even in a preparative scale. The thiophene synthesis described presents remarkable sustainability with an E ‐factor of 7.4, the solvent‐free conditions being crucial for this feature. The catalyst is straightforwardly prepared, and it is easily separated from the reaction mixture, making its reuse possible. Abstract : An ionic organic solid, such as 1, 3‐bis(carboxymethyl)imidazolium chloride, mediates the metal‐free synthesis of thiophene derivatives by favoring the reaction under solvent‐free conditions, enabling an efficient and sustainable protocol.